2022
DOI: 10.9787/kjbs.2022.54.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Studies on How Changing the Transplanting Time Affects Rice Quality and Yield

Abstract: This study was conducted to reset the transplanting period to produce high-quality rice in the South regions due to the rise in air temperature caused by global warming. From May 15 to June 25, transplants were performed five times every ten days. Quantity and quality were comprehensively reviewed, including watering season, ripened grain rate, head rice rate, head rice yield, protein content, and palatability. In the southern plains, medium-late and medium maturing cultivars yielded the most when transplanted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Previous studies showed the same trends, indicating that protein content increased as the transplanting date was delayed [24][25][26][27] and early-maturing rice varieties showed higher protein content than mid-late-maturing rice varieties even when transplanted on the same date and with the same level of fertilizer applied [47], suggesting that rice with a higher protein content has a shorter vegetative period.…”
Section: Rice Protein Contentmentioning
confidence: 60%
See 3 more Smart Citations
“…Previous studies showed the same trends, indicating that protein content increased as the transplanting date was delayed [24][25][26][27] and early-maturing rice varieties showed higher protein content than mid-late-maturing rice varieties even when transplanted on the same date and with the same level of fertilizer applied [47], suggesting that rice with a higher protein content has a shorter vegetative period.…”
Section: Rice Protein Contentmentioning
confidence: 60%
“…The grain filling stage is the period during which the rice grain is developing and filling with starch and the mean temperature during this stage can affect the physicochemical properties, starch structure, and appearance of rice grains [7][8][9][10][11][12]. In this study, there were significant differences in the head and chalky rice rates between the two rice varieties and these rates varied depending on the transplanting date since differences in the transplanting date can result in differences in temperature and sunlight exposure, which can affect the growth and development of rice plants [25][26][27] (Figure S1).…”
Section: Rice Appearance Traitsmentioning
confidence: 92%
See 2 more Smart Citations